PORTRAITS OF CHILDREN IN POETRY OF JOVAN JOVANOVIĆ ZMAJ AND ALEKSANDAR VUČO - Biserko, Ana (Metodička teorija i praksa, 2024)
Social and political conditions have always influenced literature and it was reflected on the poetry of very important poets in the development of Serbian literature for children and young people, Jovan Jovanovic Zmaj and Aleksandar Vuco.In this text we are going to think about the two different ways in which childhood was depicted in the poetry of Jovan Jovanovic Zmaj and Aleksandar Vuco.We are going to compare the first and the second period in the development of Serbian literature for children and young people analyzing the relationship between adults and children (authority and freedom),presentation of school and social reality and consequently the conditions in which children are brought up.While Zmaj’s child is overprotected by his parents, Vuco’s child is rebellious, capable of taking care of himself and finding the way out of the problems he is facing. We are going to show the way in which Vuco builds the critical attitude towards capitalism using the characterisation of his heroes and observing their everyday incidents and accidents, their imaginations and cravings. We are going to consider the values children were taught by Zmaj and ,on the other hand the values Vuco offered them as well as the elements that influenced that poetics